2021
DOI: 10.1155/2021/6697872
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity of Aspirin Eugenol Ester on Paraquat‐Induced Cell Damage in SH‐SY5Y Cells

Abstract: Aspirin eugenol ester (AEE) is a new pharmaceutical compound esterified by aspirin and eugenol, which has anti-inflammatory, antioxidant, and other pharmacological activities. The aim of this study was to investigate the protective effect of AEE on paraquat- (PQ-) induced cell damage of SH-SY5Y human neuroblastoma cells and its potential molecular mechanism. There was no significant change in cell viability when AEE was used alone. PQ treatment reduced cell viability in a concentration-dependent manner. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In addition, the JC-1 assay confirmed the increased mitochondrial membrane potential (Δψm) in LS-SLNP-pretreated SH-SY5Y cells exposed to oxidative stress and A β ,1-42 amyloid fibrils compared to LS-alone treatment. In this context, Zhang et al [ 37 ] confirmed the protective efficacy of aspirin eugenol ester against paraquat-induced toxicity in SH-SY5Y cells. Zhang et al [ 32 ] have confirmed that 3-Isoquinoline and its derivatives protect neuronal cells from beta-amyloid-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the JC-1 assay confirmed the increased mitochondrial membrane potential (Δψm) in LS-SLNP-pretreated SH-SY5Y cells exposed to oxidative stress and A β ,1-42 amyloid fibrils compared to LS-alone treatment. In this context, Zhang et al [ 37 ] confirmed the protective efficacy of aspirin eugenol ester against paraquat-induced toxicity in SH-SY5Y cells. Zhang et al [ 32 ] have confirmed that 3-Isoquinoline and its derivatives protect neuronal cells from beta-amyloid-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress is an imbalance of oxidative and antioxidant systems that leads to oxidative damage in the body [23]. Previous studies have shown that AEE can improve oxidative stress, mitochondrial dysfunction, and immune-inflammatory responses [15,19,24,25]. Several studies have demonstrated that Caco-2 cells are suitable for studies related to intestinal inflammation [8,26].…”
Section: Discussionmentioning
confidence: 99%